Philosophy for professionals. A short series of practice-orientated lectures and reader: учебное пособие для вузов - Makhamatov, T. T. Timour T. (Авторский учебник, 2022)
"East is East, and West is West, and never the twain shall meet..." Rudyard Kipling would indeed be astonished at the pace of modern globalisation, where East and West not just "meet", but, in fact, come to saturate one another in so many controversial ways... This book will help you study the DNA of "the twain", particularly emphasising on disclosing the nature of the Orient, with all its lore and wisdom, the living spirit of which may perhaps save this bleeding world one day.